Effects of OSA Surgery on Ophthalmological Microstructures. (October 2019) - Lin, Pei-Wen; Lin, Hsin-Ching; Friedman, Michael; Chang, Hsueh-Wen; Salapatas, Anna M.; Lin, Meng-Chih; Chin, Chien-Hung
Objective: Obstructive sleep apnea/hypopnea syndrome (OSA) could compromise oxygenation of the optic nerve and cause glaucomatous optic neuropathy; however, there were no studies to investigate the changes of visual function and retinal microstructures in OSA patients after upper airway surgery. We aim to assess the changes in the visual sensitivity and retinal fiber layer thickness in OSA patients before and after surgery. Methods: This prospective single-blind study enrolled patients with OSA from a tertiary academic medical center who had unsuccessful conservative therapy and then underwent surgery. The patients were referred for comprehensive ophthalmologic evaluation at baseline and 6 months after OSA surgery. The polysomnographic findings were collected pre- and postoperatively. Visual sensitivities on standard automated perimetry (SAP) were assessed. Peripapillary retinal nerve fiber layer (RNFL) thickness and macular layer (ML) thickness parameters were measured by spectral-domain optical coherence tomography (OCT). Results: A total of 108 OSA patients were enrolled. Six months after surgery, the major parameters of polysomnography (PSG), mean deviation, and pattern standard deviation of SAP significantly improved in these OSA patients. Regarding the OCT parameters, thickness of ML in the nasal-outer, superior-inner, temporal-inner, inferior-inner, nasal-inner sectors, and total ML thickness significantly increased 6 months after upper airway surgery in the severe OSA group (apnea/hypopnea index ⩾30 per hour). Conclusion: The visual sensitivities on SAP, ML thickness on OCT, and oxygenation status on PSG significantly improved 6 months after upper airway surgery in patients with severe OSA. Upper airway surgery may ameliorate the microstructures of the retina in patients with severe OSA.